Feasibility and safety of day care laparoscopic cholecystectomy in a developing country. Issue 931 (1st May 2003) - Bal, S; Reddy, L G S; Parshad, R; Guleria, R; Kashyap, L
Abstract : Background: Although day care laparoscopic cholecystectomy (DCLC) has been shown to be safe in centres with adequate infrastructure for day care surgery, its feasibility and safety in developing countries has never been studied. Because of differences in the quality of health care delivery, western guidelines for day care surgery cannot be universally applied to developing countries. Patients and methods: Patients less than 65 years who were graded I and II on the American Society of Anesthesiologists physical status score, irrespective of their educational status, living within 20 km, and willing to make their own arrangements for a return to hospital in case of problems were selected for DCLC. Follow up was done by patients calling the hospital the morning after surgery. Results: 50% of the eligibility criteria were new; 313/383 patients were suitable for DCLC. The commonest cause for rejection was that the patient lived out of the defined area (50%). Altogether 92% were discharged within eight hours of surgery. The reasons for failure to discharge were the presence of abdominal drains in four (2%), nausea and vomiting in nine (3%), and conversion to open surgery in five (2%). Ten patients (3%) were readmitted; of these only two (<1%) had complications needing re-exploration. Analysis of results showed that the inclusion and discharge criteria were valid and that the readmission and complication rates as well as the ease and accuracy of follow up were comparable to published data. DCLC reduced waiting times and increased patient turnover and may have a positive impact on resident training. Conclusions: DCLC is safe, feasible, and has potential benefits for health care delivery in developing countries. Each surgical service needs to develop their own guidelines based on local patient demography.